EVALUASI DAMPAK PENGGUNAAN SISTEM PEMBAYARAN DIGITAL DAN PENGENDALIAN DIRI TERHADAP PERILAKU MENABUNG GENERASI Z STUDI KASUS PADA MAHASISWA DI KOTA MAKASSAR - Nur Arini Susanti; Nurdjanna Fadjrin Uluputty; Maya Muliani (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2025)
This study aims to determine the impact of the use of digital payment systems and self-control on the savings behavior of generation Z among students in Makassar City. The method used in this study is a quantitative approach with multiple linear regression analysis techniques. The sample in this study was 277 respondents selected using purposive sampling techniques. Data were obtained through questionnaires and processed using IBM SPSS Statistics 27. The findings of this study indicate partial testing that 1) there is a significant influence of digital payments on the savings behavior of generation Z among students in Makassar City, 2) there is a significant influence of self-control on the savings behavior of generation Z among students in Makassar City, 3) simultaneous testing shows that digital payments and self-control have a significant effect on the savings behavior of generation Z among students in Makassar City.